ANALISIS PENGARUH CAPITAL ADEQUACY RATIO (CAR), NET INTEREST MARGIN (NIM), LOAN TO DEPOSIT RATIO (LDR), NON PERFORMING LOAN (NPL) DAN BOPO TERHADAP PROFITABILITAS BANK PERSERO DI INDONESIA PERIODE 2005-2012 - Johar Manikam; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2013)
This research is performed in order to test the influence of the CAR (Capital Adequacy Ratio), NPL (Non Performing Loan), BOPO, NIM (Net Interest Margin), and LDR (Loan to Deposit Ratio) toward bank profitability that proxied by Return On Assets (ROA).This research is include all of National General Banking in Indonesia who provide financial report during period 2005 through 2012. The data is based on bank’s annual report since 2005 to 2012. Analysis technique used is a classic assumption test covering normality test, multicolinierity test, heteroscedastisity test and autocorrelation test. Others were done doubled linear regression test with smallest square equation and hypothesis test use t-statistic to test coefficient of regression partial in level of significance 5%. The result of normality test show the data research was normally distributed. Based on multicolinierity test, heteroscedastisity test, and autocorrelation test the deviate variable of classic assumption has not founded. The Result shows BOPO, NIM and NPL has significant effect toward bank profitability.